ChemInform Abstract: Cross‐Dehydrogenative Coupling Reaction Using Copper Oxide Impregnated on Magnetite in Deep Eutectic Solvents. Issue 24 (27th May 2016) - Marset, Xavier; Perez, Juana M.; Ramon, Diego J.
Abstract: Various tetrahydroisoquinoline derivatives are prepared by a cross‐dehydrogenative coupling reaction using choline chloride/ethylene glycol (1:2) as a deep eutectic solvent (DES).